Molecular Characterization of the Tumor Suppressor Candidate 5 Gene: Regulation by PPARγ and Identification of TUSC5 Coding Variants in Lean and Obese Humans - Trina A. Knotts; Hyun Woo Lee; Jae Bum Kim; Pieter J. Oort; Ruth McPherson; Robert Dent; Keisuke Tachibana; Takefumi Doi; Songtao Yu; Janardan K. Reddy; Kenji Uno; Hideki Katagiri; et al. (PPAR Research)
Tumor suppressor candidate 5 (TUSC5) is a gene expressed abundantly in white adipose tissue (WAT), brown adipose tissue (BAT), and peripheral afferent neurons. Strong adipocyte expression and increased expression following peroxisome proliferator activated receptor γ (PPARγ) agonist treatment of 3T3-L1 adipocytes suggested a role for Tusc5 in fat cell proliferation and/or metabolism. However, the regulation of Tusc5 in WAT and its potential association with obesity phenotypes remain unclear. We tested the hypothesis that the TUSC5 gene is a bona fide PPARγ target and evaluated whether its WAT expression or single-nucleotide polymorphisms (SNPs) in the TUSC5 coding region are associated with human obesity. Induction of Tusc5 mRNA levels in 3T3-L1 adipocytes by troglitazone and GW1929 followed a dose-response consistent with these agents' binding affinities for PPARγ. Chromatin immunoprecipitation (ChIP) experiments confirmed that PPARγ protein binds a ∼−1.1 kb promotor sequence of murine TUSC5 transiently during 3T3-L1 adipogenesis, concurrent with histone H3 acetylation. No change in Tusc5 mRNA or protein levels was evident in type 2 diabetic patients treated with pioglitazone. Tusc5 expression was not induced appreciably in liver preparations overexpressing PPARs, suggesting that tissue-specific factors regulate PPARγ responsiveness of the TUSC5 gene. Finally, we observed no differences in Tusc5 WAT expression or prevalence of coding region SNPs in lean versus obese human subjects. These studies firmly establish the murine TUSC5 gene locus as a PPARγ target, but the significance of Tusc5 in obesity phenotypes or in the pharmacologic actions of PPARγ agonists in humans remains equivocal.